Facing love addiction : giving yourself the power to change the way you love - Mellody, Pia; Miller, Andrea Wells; Miller, Keith (HarperOne, 2003)
Describes the dynamics of a coaddicted relationship, the symptoms of each partner, and the stages of addiction and provides a practical recovery process for love addicts.